Bibliography of Ethiopian Semitic, Cushitic, and Omotic Linguistics XXIII: 2019 - Bulakh, Maria; Hummel, Susanne; Panini, Francesca (Aethiopica, 2020)
Bibliography of Ethiopian Semitic, Cushitic, and Omotic Linguistics XXIII: 2019